2015
DOI: 10.1186/s12905-015-0272-4
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in Iranian women with polycystic ovary syndrome: a qualitative study

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is associated with a range of challenging symptoms which impact patient’s lives. Iranian women with PCOS are likely to face a number of unique difficulties given particular societal and cultural norms for women. Understanding health-related quality of life (HRQoL) from a patients’perspective is critical to developing the appropriate support interventions. The present study aimed to generate an in-depthunderstanding of HRQoL Iranian women with PCOS.MethodsTwenty Irania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
1
21
0
2
Order By: Relevance
“…Having a chronic course, PCOS has a negative impact on the quality of life over years. Moreover, PCOS may occur concurrently with hyperandrogenism, hyperinsulinemia, and glucose intolerance, leading to conditions such as infertility, recurrent spontaneous abortions, hyperlipidemia, type 2 diabetes mellitus, hypertension, coronary atherosclerosis, endometrial hyperplasia, and endometrial cancer [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Having a chronic course, PCOS has a negative impact on the quality of life over years. Moreover, PCOS may occur concurrently with hyperandrogenism, hyperinsulinemia, and glucose intolerance, leading to conditions such as infertility, recurrent spontaneous abortions, hyperlipidemia, type 2 diabetes mellitus, hypertension, coronary atherosclerosis, endometrial hyperplasia, and endometrial cancer [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in one study, 14 % of women suffering from PCOS reported suicidal ideation. 8 In present study, all the participants rated an improvement in overall well-being and quality of life.…”
Section: Discussionmentioning
confidence: 95%
“…Menstrual irregularities have consequences on women's intimate relations, cultural and social concerns and other aspects of their reproductive and general health.8 Studies in different cultural settings have suggested that menstrual problems are one of the greatest concerns reported by women suffering from PCOS. 8 An overall improvement in menstrual health at the end of this program is definitely a positive step towards improving the quality of life in women diagnosed with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Amiri, Tehrani, Esmailzadeh, Tohidi, Azizi and Basirat in 2018 [9] calculated the relationship between PCOS and Sexual function and found that 45.75% of the PCOS women met the criteria for sexual dysfunction. The literature suggests that the physical, medical and psychological symptoms of PCOS significantly affect the quality of life and satisfaction with life of such women [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%